Makna Pesan Nonverbal dalam Tayangan Kartun Larva Season 3 Episode Garlic 1 dan 2 - Meidyastuti, Revi Tria; Jupriono, Jupriono; Rusmana, Dewi Sri Andika (representamen, 2020)
Silent animation is an animation that was created without using sound recording, especially in dialogue. The greatest strength of silent animation is nonverbal communication which is all forms of gestures that are not words. This research attempts to examine Larva season 3  episode Garlic 1 and 2 by using the theory of nonverbal systems of kinesis and proxemics categories as a reference unit of analysis. This research aims to interpret the meanings of nonverbal messages by using the Gillian Rose visual methodology from site of self and site of production to find the meanings of nonverbal messages in Larva season 3 episode Garlic 1 and 2. The research uses a critical paradigm with a qualitative approach that focuses on scenes that are describing nonverbal messages in Larva visualization. The results had found that the meanings of nonverbal messages displayed in Larva season 3 episode Garlic 1 and 2 also reflected in recent life issues such as struggling, respecting others, earnest, and being patient. Keywords: Nonverbal Messages, Kinesis, Proxemics, Visual Methodology